Effects of Dipeptidyl-Peptidase 4 Inhibitor about Vascular Inflammation in a Metabolic Syndrome Model - Renna, Nicolas Federico (2014)
Background: In this study, we used vidagliptin(V) to examine the role of the DDP-IV, incretin system component, in the activation of different molecular inflammatory cytokines, NF-kB and VCAM-1 to generate a microenvironment that supports cardiovascular remodeling. Methods: Male WKY and SHR were separated into five groups: Control, FFR: WKY rats receiving a 10% (w/v) fructose solution during all 12 weeks, SHR, FFHR: SHR receiving a 10% (w/v) fructose solution during all 12 weeks and FFHR+V: (5 mg/kg per day for 6 weeks) (n = 8 each group). Metabolic variables and systolic blood pressure were measured. The TBRAS, eNOS activity, and NAD(P)H oxidase activity were estimated to evaluate oxidative stress. Cardiac and vascular remodeling were evaluated. To assess the cytokine, NF-kB and VCAM-1 immunostaining techniques were used. Results: The FFHR experimental model presents metabolic syndrome criteria, vascular and cardiac remodeling, vascular inflammation due to increased expression of NF-kB, VCAM-1, and pro-atherogenic cytokines. Chronic treatment with V was able to reverse total or partiality of variables studied. Conclusions: Data demonstrated an important effect of DDP-IV in reducing vascular inflammation, accompanied by a favorable reduction in metabolic and structural parameters.